(untitled) (Theatrum historiae, 2007)
The article discusses the question of sources and their processing in parts dealing with ancient Greeks in the Carion’s World Chronicle, first published in 1532 in Wittenberg. The first version of this historical textbook was published in German but translations into many European languages appeared soon, including two Czech translations. Later, a more influential, reworked and enlarged Latin version was published by a Lutheran theologist Philipp Melanchthon and his nephew Caspar Peucer who continued his work after Melanchthon’s death. There is a dispute among scholars over the Melanchthon’s participation in the first German version. According to Gotthard Münch’s treatise, this article supposes Melanchthon’s authorship of the whole part dealing with the ancient history. Especially the Greek sections reveal that their author employed, besides medieval and humanistic chronicles, primarily many original Greek sources, that were already at disposal at that time. Also moral instructions are systematically added in the endings of the stories. These parts are clearly not compilations of the preceding medieval or early humanistic chronicles by an astrologer Johan Carion, who, apart from this chronicle, did not focus on history, but a deliberate piece of work by a Greek expert and a moralist such as Melanchthon. This idea is supported by the fact that the concept of Greek history in Melanchthob’s later Latin version of the chronicle is the same as in the first German version. Also the chronological framework is the same. In comparison with the preceding world German chronicles, as that of Schedel, Nauclerus or Franck, it is obvious that Melanchthon, in view of his concept of history, deliberately excludes all the fantastic elements, for example Amazones, a fable folk of warlike women, to which other chronicles pay much attention, for in Melanchthon’s view history should be a collection of good and bad examples. The article shows that Melanchthon often produced his exempla by radical transformation of the stories found in the ancient texts. Transformation is not only due to his moralism but also due to his monarchic perspective connected with the conviction that hereditary rulers have their legitimacy from the God. This is the most transparent in his interpretation of the subjugation of Greece by Phillip the Macedon. This act is not seen as the end of old and famous freedom of Greece, as seen by Nauclerus and his source Justinus, but as the establishment of order between the fighting Greek towns.